Analysis on Thermodynamic and Thermoelectric Effects of Hot Carrier Solar Cells Barriers in Nanowires - Toma,Alexandru (2025)
This thesis focuses on developing energy barrier models that increase photovoltaic hot carrier extraction efficiency. Hot carriers are electrons containing an excess of kinetic energy and the energy required to leave the valence band. In mitigating losses and increasing the efficiency of solar cells, hot carriers offer the opportunity to extract this kinetic energy. The study of extracting the kinetic energy has resulted in looking at nanowires with heterostructures, comprised of type III-V semiconductor materials [1]. The nanowires have an energy barrier that allows only the hot carriers to travel over or tunnel through. Studying the effects of different barriers on hot carrier flow provides insight into how to increase efficiency. The first half of this thesis is concerned with introducing the concept of photovoltaic solar cells and the transition into hot carriers. We describe their role in band gap physics, pivoting to their role in photovoltaic devices. We introduce a base of equations and descriptions for how to model electron transport in a nanowire system. However, the focus here is to build a foundation in the theory. Therefore, the models explored through this work are all in one dimension. The Landauer-Buttiker scattering theory approach towards mapping pieces of efficiency (maximum power output, fill factor) is the main method of describing hot carrier flow in this work. The other half of this work is concerned with introducing the models explored during this thesis work. We look at a benchmark rectangular model, testing its length limits in the infinite and finite regimes. Additionally, we explore one more infinite length model to reinforce knowledge of the system, followed by a physical rectangular and a rectangle/triangle hybrid model. We present our results, seeing which model best gives rise to a positive correlation in maximizing efforts. The hybrid model presents a possible solution towards optimizing both power and fill factor for physical experimentation. Understanding how to characterize hot carrier transport in nanowires at the fundamental level allows for further developments in the field of hot carrier physics and is an important contribution to future experiments.
Keywords: solar-cells; hot carriers; quantum transport; Landauer-Buttiker; Scattering; fermi-distribution; solid state physics; solar energy conversion; III−V nanowire heterostructures; master thesis; theoretical physics